Impact of social isolation on the level of sports training of young athletes, caused by COVID 19 - Luiz Felipe Silva; Paulo Francisco de Almeida-Neto; Alexandre Bulhões Correia; Victor Sabino de Queiros; Dihogo Gama Matos; Daniel Dalmau; Paulo Moreira Silva Dantas; Breno Guilherme de Araújo Tinoco Cabral (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2021)
Social distancing towards prevention of the outspread of COVID-19 pandemics in the year of 2020 may significantly contribute towards physical inactivity of citizens worldwide. The objective of the current study was to quantify the impact of such preventive measure over the physical activity level of young Brazilian athletes across several sporting areas. Sixty-eight (68) Brazilian athletes (14.7 ± 1.68 years) answered to adapted version of the International Physical Activity Questionnaire (I-PAQ) through an online platform. It was requested that participants reported on their level of physical activity before and during the social distancing period. 67.7% of interviewed athletes stated being able to adapt their sports training to their isolation environment under a physical education professional`s distance guidance. Only 4.38% of the sample were not training under such a supervision and therefore inactive. Therefore, despite social distancing, the sampled athletes seem to remain physically active.